2002
DOI: 10.1177/002215540205000307
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Temporospatial Expression of Postnatal Porcine Skeletal Myosin Heavy Chain Genes

Abstract: S U M M A R Y Postnatal skeletal muscle fiber type is commonly defined by one of four major myosin heavy chain (MyHC) gene isoforms (slow/I, 2a, 2x, and 2b) that are expressed. We report on the novel use of combined TaqMan quantitative real-time RT-PCR and image analysis of serial porcine muscle sections, subjected to in situ hybridization (ISH) and immunocytochemistry (IHC), to quantify the mRNA expression of each MyHC isoform within its corresponding fiber type, termed relative fiber type-restricted expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 27 publications
(29 reference statements)
1
32
0
Order By: Relevance
“…Each cDNA template for RT-PCR was prepared from mRNA extracted from 50 mg of LM tissue collected within 30 min after exsanguination (Trifast, Peqlab Biotechnologie GmbH, Erlangen, Gemany), by first-strand reverse transcription using 0.50 μg of oligo-d(T) (Improm-II reverse transcriptase, Promega, Mannheim, Germany) in a final volume of 20 µl. All used primers and taqman probes (Supplementary Table S1) are published by da Costa et al (2002). The TaqMan PCR assays for each target gene were performed in triplicate on cDNA templates with a Rotor-Gene 6500 QRT-PCR thermocycler analyser (Corbett Life Science, Sydney, Australia) according to the manufacturer's recommendations.…”
Section: Experimental Design Animals and Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Each cDNA template for RT-PCR was prepared from mRNA extracted from 50 mg of LM tissue collected within 30 min after exsanguination (Trifast, Peqlab Biotechnologie GmbH, Erlangen, Gemany), by first-strand reverse transcription using 0.50 μg of oligo-d(T) (Improm-II reverse transcriptase, Promega, Mannheim, Germany) in a final volume of 20 µl. All used primers and taqman probes (Supplementary Table S1) are published by da Costa et al (2002). The TaqMan PCR assays for each target gene were performed in triplicate on cDNA templates with a Rotor-Gene 6500 QRT-PCR thermocycler analyser (Corbett Life Science, Sydney, Australia) according to the manufacturer's recommendations.…”
Section: Experimental Design Animals and Feedingmentioning
confidence: 99%
“…In the present study, the mean slope of the six genes was − 3.37 ± 0.25. The relative standard curve method was used to quantify the relative gene expression of embryonic, perinatal, slow/I, IIA, IIX, IIB MyHC isoforms and of β-actin as described by da Costa et al (2002). To correct for variations in the quality and quantity of cDNA templates, all MyHC isoform expression results were normalized to corresponding endogenous β-actin mRNA levels, which within each muscle were not affected by treatment (P ⩾ 0.42).…”
Section: Experimental Design Animals and Feedingmentioning
confidence: 99%
“…A recent study suggests that in the genome of some species, such as the horse, only a pseudogene with a sequence similar to that of the MHC-2B gene is present (Chikuni et al, 2004a). There are, however, exceptions: in pigs, the 2B isoform is expressed at the protein level in several skeletal muscles, generally in hybrid 2X/B fibres (Da Costa et al, 2002;Toniolo et al, 2004), and in cattle we have recently shown the expression of MHC-2B at the mRNA level in extraocular muscles .…”
mentioning
confidence: 99%
“…Four out of eight isoforms of MyHC genes known in mammals have been identified in porcine muscle (Chang and Fernandes, 1997). Immunohistochemistry (Graziotti et al, 2001;da Costa et al, 2002;Lefaucheur et al, 2004), in situ hybridization (Graziotti et al, 2001;da Costa et al, 2002;Lefaucheur et al, 2004) and electrophoresis (Bee et al, 1999) have been used to examine muscle fibre typing essentially based on the discrimination of MyHC isoforms. Newly developed real-time PCR assays have been reported to distinguish four isoforms in pig skeletal muscle (da Costa et al, 2002;Lefaucheur et al, 2004).…”
mentioning
confidence: 99%
“…Immunohistochemistry (Graziotti et al, 2001;da Costa et al, 2002;Lefaucheur et al, 2004), in situ hybridization (Graziotti et al, 2001;da Costa et al, 2002;Lefaucheur et al, 2004) and electrophoresis (Bee et al, 1999) have been used to examine muscle fibre typing essentially based on the discrimination of MyHC isoforms. Newly developed real-time PCR assays have been reported to distinguish four isoforms in pig skeletal muscle (da Costa et al, 2002;Lefaucheur et al, 2004). Frequencies of fibres determined by muscle fibre staining for ATPase and relative abundance of MyHC isoforms determined by quantitative reverse transcription-PCR of corresponding pairs of type I, IIa and IIx/IIb were correlated (r 5 0.71, 0.67 and 0.52, respectively) Wimmers et al, 2008).…”
mentioning
confidence: 99%